2020
DOI: 10.1186/s12904-020-00581-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, confidence, and educational needs of palliative care in nurses caring for non-cancer patients: a cross-sectional, descriptive study

Abstract: Background: Palliative care is a patient-centred, integrated approach for improving quality of life for both patients facing life-threatening illnesses and for their families. Although there has been increased interest in palliative care for non-cancer patients, the palliative care competency of nurses who care for non-cancer patients has rarely been investigated. This study described the palliative care knowledge, attitude, confidence, and educational needs in nurses who care for patients with congestive hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
51
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 47 publications
(72 reference statements)
13
51
0
5
Order By: Relevance
“…Having adequate knowledge of hospice care was also a factor that affected the nurses’ attitudes toward hospice care, which is consistent with the research of Kim et al 24 They showed that the knowledge of hospice care of nurses was significantly correlated with their attitudes, training in hospice care, palliative care, and death care. 24 Nurses with sufficient knowledge of hospice care may be more able to understand death from a scientific and humane perspective and establish a healthy outlook on life and death. This would enable them to actively treat terminally ill patients, help patients to accept the natural law of life, and provide patients and their families with adequate hospice care, and mental and psychological support.…”
Section: Discussionsupporting
confidence: 89%
“…Having adequate knowledge of hospice care was also a factor that affected the nurses’ attitudes toward hospice care, which is consistent with the research of Kim et al 24 They showed that the knowledge of hospice care of nurses was significantly correlated with their attitudes, training in hospice care, palliative care, and death care. 24 Nurses with sufficient knowledge of hospice care may be more able to understand death from a scientific and humane perspective and establish a healthy outlook on life and death. This would enable them to actively treat terminally ill patients, help patients to accept the natural law of life, and provide patients and their families with adequate hospice care, and mental and psychological support.…”
Section: Discussionsupporting
confidence: 89%
“…28 Moreover, knowledge levels remain low among health care professionals regarding patients who are receiving palliative care. 29 The result of this study showed that education and training program is not the only key factor to be initiated to improve the quality of EMS service for palliative care patients. The healthcare system, the EMS system, the national policy and patients' awareness are also crucial factors for driving change in EMS practice.…”
Section: Discussionmentioning
confidence: 89%
“… 28 Moreover, knowledge levels remain low among health care professionals regarding patients who are receiving palliative care. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Palliative nursing care is a nursing intervention approach for patients who have chronic diseases and prolonged suffering condition (World Palliative Care Alliance, 2014), (Rodin et al, 2020). Nurses have the main competence that are caring for patients and their families and make benchmarks for the professionalism of nurses that consist of empathy, therapeutic communication skills, and patient-centered care (Griffiths et al, 2012), (Kim et al, 2020). Caring is a basic concept of nursing that includes interpersonal interpretation of patients with some characteristics such as professional knowledge, skills, professional maturity and nurse sensitivity (Drahošová & Jarošová, 2016).…”
Section: Introductionmentioning
confidence: 99%